Kepatuhan WPOP: Dapatkah Kesadaran Berperan sebagai Mediasi? - Hanafiah Widhiatmoko; Arya Samudra Mahardhika (Politeknik Ganesha Medan, 2023)
Tax is one of the largest state revenues which plays an important role in the growth of a country. Therefore, the factors that contribute to the success of tax revenues are always interesting to observe. The purpose of this research is to analyze the influence of Knowledge, Awareness and Religiosity on Individual Taxpayer Compliance, besides that this research also tries to analyze the role of Awareness as a mediating variable for Individual Taxpayers. This type of research was causal quantitative using primary data obtained by distributing questionnaires to individual taxpayers, and 115 people were used as respondents for research. The hypothesis in this study was tested using multiple linear regression, as well as the Sobel test to test the mediating variable. The results of testing the coefficient of determination (R2) obtained the Adjusted R Square value which indicates that Taxpayer Compliance is influenced by the variables Knowledge, Awareness and Religiosity of 58.3% while the rest is influenced by other variables not included in this research model. The results of testing the hypothesis in this study provide empirical evidence that Knowledge and Awareness have a significant positive effect on Taxpayer Compliance, while Religiosity has no effect on Taxpayer Compliance. Based on the Sobel test, awareness is able to mediate the effect of knowledge on compliance and the effect of religiosity on individual taxpayer compliance.